Climate change and its nexus with human nutrition: An educational primer - Gonsalves, Julian; Morada, Jhon Christian; Monville Oro, Emilita; Rosimo, Magnolia; Anunciado, Ma. Shiela; Katooro, Pamela Nyamutoka; Damenu, Zerihun Lemma; Or, Thy; Kaliisa, Robert; Hailu, Getu; Umali, Diana Jean; Del Rio, Susan; et al. (2025)
Sustainability of food systems is adversely affected by biodiversity losses, climate change, and short-sighted agricultural practices. Climate change invariably affects the quality of agricultural produce resulting from increased residues and the reduction of product quality. The poor are more vulnerable because of structural inequities, their natural asset base, and risks from adverse weather. The direct and indirect impacts of climate change on nutritional value are discussed. The pitch for healthy and diverse diets has to be accompanied by biodiverse and regenerative food production systems. This educational primer is based on desk research (with key messages and links listed on each page) and is targeted to program planners, designers, and development administrators.